Propuesta de implementación para dotar de servicios triple – play por medio de la tecnología GPON a la Parroquia de Nono – Provincia de Pichincha - Morillo Ruano, Andrea Gabriela (2017)
In this paper describe the design of a fiber optic network for the Parroquia of Nono - Province of Pichincha, which provide triple play services to the habitants, provide Internet, telephony and television services, considering the following parameters: power, attenuations, distances, division levels, etc., Too refer devices that work on GPON architecture. It do analysis performed for establishing the best method of access to the parish and to observe the comparative detail of the PON technologies and their architectures, together with the standards that should be considered for the design of this network. For the simulation of network GPON is used the Optisystem software, which allows data parameterization and analysis comparative to different distances, considering that total fiber link is 20Km like an optical standard for GPON, for the distribution of communications devices have splited in two zones, zone 1 corresponds to the central population, where the most population habitant at this located and zone 2 included haciendas and hotels, these are the reference have been taken from the OLT Up the nearest user and the farthest user to perform the calculations in reference to the attenuation and the power of the signal. The goal is provide access to de media services of the population that habitat in this sector, the services are voice, video and data to high quality.